2003
DOI: 10.1016/s0008-6363(02)00646-6
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species regulate FLICE inhibitory protein (FLIP) and susceptibility to Fas-mediated apoptosis in cardiac myocytes

Abstract: FLIP, an inhibitor of apoptosis induced by cytokines of TNF family, contributes at least partly to Dox-induced sensitization to Fas-mediated apoptosis in cardiac myocytes. The expression of FLIP in cardiac myocytes is regulated by ROS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(89 citation statements)
references
References 44 publications
7
80
1
1
Order By: Relevance
“…ROS mediate Wit A-induced c-FLIP down-regulation by inhibiting NF-κB signaling pathways ROS down-regulate c-FLIP levels and increase the sensitivity to apoptotic stimuli [23,24]. As shown in Fig.…”
Section: Down-regulation Of C-flip Also Contributes To Wit A-stimulatmentioning
confidence: 89%
“…ROS mediate Wit A-induced c-FLIP down-regulation by inhibiting NF-κB signaling pathways ROS down-regulate c-FLIP levels and increase the sensitivity to apoptotic stimuli [23,24]. As shown in Fig.…”
Section: Down-regulation Of C-flip Also Contributes To Wit A-stimulatmentioning
confidence: 89%
“…Almost a decade ago, studies of cardiac myocytes showed a requirement for ROS generation by doxorubicin to trigger a loss of c-FLIP protein and subsequent sensitization of cells to Fas-induced apoptosis (48). A later study demonstrated that Fas ligand generated ROS in normal lung epithelial cells through activation of Rac1 and the NADPH oxidase.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, rat-derived embryonic cardiomyocytes, which are normally resistant to FAS-L induced apoptosis [41], may get sensitized to FAS-L when pre-exposed to DOX [49,50]. Interestingly, DOX pre-exposure may also induce increased FAS-L released by rat-derived embryonic cardiomyocytes [41], suggesting a DOX-sensitization dependent autocrine/paracrine mechanism for cardiac apoptosis induction.…”
Section: Does Dox Exposure Change Apoptosis Likelihood To Later Somatmentioning
confidence: 99%
“…This work has been supported by the Bijzonder Onderzoeksfonds of the KU Leuven (PF/10/014) to H. J. H. shown to release FAS-L after DOX [41] while getting also sensitized to DOX and respond to it in an auto/paracrine manner [49]. (E) Due to the absence of cytochrome-c in the mitochondrial inter membrane space, MOMP can lead to a bioenergetics crisis with loss of mitochondrial polarization, reduced ATP production, failure of ionic homeostasis.…”
Section: Acknowledgementmentioning
confidence: 99%
See 1 more Smart Citation